1993
DOI: 10.7326/0003-4819-119-10-199311150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Immune Globulin Prophylaxis in Liver Transplantation

Abstract: CMVIG reduced the rate of severe CMV-associated disease in patients undergoing orthotopic liver transplantation. No effect of CMVIG on CMV donor-positive, recipient-negative liver transplant recipients was shown, suggesting a need for additional prophylactic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(75 citation statements)
references
References 14 publications
0
74
0
1
Order By: Relevance
“…(34) comparing high dose acyclovir to "preemptive" ganciclovir at the time of viral shedding demonstrated similar rates of infection in the acyclovir arm. Another study reported by Snydman et al (35) noted a virtually identical infection and disease rate in their placebo patients. This raises serious doubt as to whether acyclovir has any effect by itself or following the early course of ganciclovir.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…(34) comparing high dose acyclovir to "preemptive" ganciclovir at the time of viral shedding demonstrated similar rates of infection in the acyclovir arm. Another study reported by Snydman et al (35) noted a virtually identical infection and disease rate in their placebo patients. This raises serious doubt as to whether acyclovir has any effect by itself or following the early course of ganciclovir.…”
Section: Discussionmentioning
confidence: 92%
“…EnhanCing the immune response by vaccination or by passive immunization haa reduced the incidence of CMV disease in renal transplant recipients (11,12). Though passive administration of a high titer CMV immunoglobulin has been reported recently to reduce the incidence of CMV disease and associated mortality after liver transplantation, it was not commercially available when this trial was perfonned ( 13), Despite the lack of therapeutic activity against CMV, high dose intravenous or oral acyclovir has been reported to prevent CMV disease in renal and bone marrow transplant patients without adverse effects on patient or graft survival <14, 15). Although no similar prospective trials have been reported in liver transplant recipients, an uncontrolled study showed no decrease in CMV disease with high dose oral acyclovir.…”
mentioning
confidence: 99%
“…0,01 0,1 1 10 100 1.000 Bailey et al 1993Boland et al 1993Bordigoni et al 1987Bowden et al 1986Bowden et al 1991Cofer et al 1991Condie et al 1984Fehir et al 1989Feinstein et al 1999Greger et al 1986Grundmann et al 1987Kasiske et al 1989Metselaar et al 1989Meyers et al 1983Peraldi et al 1996Ringden et al 1987Rostaing et al 1997Ruutu et al 1997Saliba et al 1989Snydman et al 1987Snydman et al 1993Steinmüller et al 1990Stippel et al 1991Sullivane et al 1990Winston et al 1982Winston et al 1987Winston et al 1993 all studies Generell sind die Ergebnisse unter CMVIG Prophylaxe besser als unter IVIG Prophylaxe. Dies gilt insbesondere für CMV-Erkrankung aber auch für die Mortalität.…”
Section: Metaanalyseunclassified
“…[9] Prophylactic CMVIG has decreased the rates of both CMV disease and CMV pneumonitis rates by 50%, leading to a concomitant decrease in the average length of hospital stay for liver transplant recipients. [10] In addition, a recent meta-analysis of CMVIG use in solid organ transplant recipients demonstrated a lower incidence of CMVassociated death and clinically significant disease in subjects who received CMVIG-based CMV prophylaxis [11]. However, other studies have found no significant impact of CMVIG on the incidence of CMV disease after liver transplant [12].…”
Section: Introductionmentioning
confidence: 99%